Effect of annealing and process parameters on microstructure and properties of DC Magnetron Sputtered Ni-Zr alloy thin films. (30th January 2017) - Sahu, Bibhu P.; Mitra, Rahul
ABSTRACT: Ni-Zr alloy thin films were processed by DC magnetron sputtering of high purity Ni and Zr targets in ultrahigh vacuum at ambient temperature, with the substrate being subjected to either 0 V or -60 V bias. Some of the as-deposited films were annealed in vacuum at 700 ° C for 1 h. Surface profilometer and atomic force microscope were used to measure the film thickness and surface roughness, respectively. X-ray diffraction and cross-sectional TEM analysis have shown dispersion of nano-sized Ni3 Zr dispersed in nanocrystalline Ni matrix. Nano-indentation and scratch tests conducted at 2 mN load have shown variation of hardness, Young′s modulus, scratch resistance, and coefficient of friction with substrate bias and annealing due to changes in grain size and surface roughness.